Urology during a Crisis: A Management Algorithm - Papaefstathiou, Efstathios; Apostolopoulou, Aikaterini; Papaefstathiou, Eirini; Moysidis, Kyriakos; Hatzimouratidis, Konstantinos; Sarafis, Pavlos (My University, 2020)
As of March 11, 2020, Coronavirus disease (COVID-19) has been declared a pandemic from WHO organization. On June 30, 2020, the disease has already spread in all continents numbering 10 million confirmed cases and 500.000 deaths(1). In regions with limited cases, health-care units suffice to provide routine services and manage infected with coronavirus patients simultaneously. However, during an epidemic outbreak, the high number of cases compared to the shortage of health workforce increases the risk of system collapse. In order to respond adequately, hospitals should reprioritize their services, including operations and outpatient clinics and protect its personnel from infection(2) Shrinkage of surgical activity in emergency surgeries saves equipment and personnel necessary for the care of COVID-19 patients and protects high risk patients from getting infected(3). In order to maximize the provided urological surgeries, 4 parameters should be considered: the emergency of the operation, the risk of infection, the capacity of the hospital and cooperation between different urological departments. Initially, all emergency surgeries should be performed promptly in order to ameliorate the health status of the patient and reduce hospital stay (Table 1). In case the results of COVID-19 test, are not readily available the operation should be performed without delay in special operating rooms and the patient treated in separate wards. Regarding elective operations, all non-oncological surgeries should be postponed. In oncological diseases, where possible, opt for alternative treatments, such as radiotherapy with ADT in prostate cancer or ablation of renal tumors. Next, all surgical candidates should be tested for COVID-19 before surgery. In case of positive result, the surgery should be rescheduled. In countries where this measure is not feasible, preoperative evaluation of the respiratory tract from an internist, including a chest x-ray is suggested. Following that, the operating program should be adapted to hospital capacities. In case of small number of COVID-19 cases, surgical candidates should continue to be treated according to oncological severity. On the contrary, when hospital capabilities are overwhelmed by the inflow of COVID-19 patients consider treating patients with the longest expected survival, irrespective of the underline disease. Otherwise, urologist must consider maximizing the number of treated patients and minimizing the hospital stay, possibly by performing less time-consuming surgeries particularly in patients without good performance status. The expertise of each center should also be evaluated and candidates for radical, time-consuming operations referred to specialized centers (Figure 1). During de-escalation phase, special attention should be given in patients with urolithiasis and ureteral stents, since they are at increased risk of encrustation and complicated pyelonephritis (4). All previous measures could reduce attendance in hospitals with the cost of increasing waiting lists. Despite, closure of outpatient departments prevents crowding and hinders dispersion of the virus(5), the demand for urological services is ongoing and, also expected to increase during the de-escalation phase of COVID-19 pandemic. However, there is no single protocol in the management of urological patients. In order to preserve general population healthy and face current demands the urologist should consider the following questions (Figure 2). 1. Is this case an emergency? In order to provide consultation in urological patient urologists are encouraged to use telemedicine(6). Through video-communications urologist can diagnose effectively common urological disease and even prescribe medications and tests. Additionally, urologists can screen patients with acute urological problems and symptoms of COVID-19 infection referring appropriately. Particularly patients at increased risk for severe COVID-19 pneumonia such as renal transplant patients, oncological patients and those with renal dysfunction should have their clinical evaluation through telemedicine(7). On the contrary, the inability to perform clinical and diagnostic tests, along with the lack of experience in teleconsultation lowers diagnostic accuracy. 2. Is there a possibility of COVID-19 infection? Screening for COVID-19 is necessary for all urological patients. Regarding outpatients, phone screening about respiratory symptoms within the last 14 days (fever, cough, myalgia, fatigue, dyspnea), travel history and fever could detect high risk patients requiring further referral to special units.
Keywords: Management protocol; Prioritization of surgeries; COVID-19; Urological patients